MARKETING TURÍSTICO - de la Colina, Juan Manuel; -Compilación CEO, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2010)
Abstract. Marketing is that one human activity directed to satisfy needs and desires by means of processes with interchange. The academic concept of Marketing would include the following fundamental ideas nowadays: - The direction of Marketing is a function of the companies including in its strategic planning. - The four fundamental activities for the development of the previous function turn around decisions on products, prices, communication and distribution. - The interchange does not underlie only in the goods and services, but any class of interchanges of values is included, which implies to extend the object of Marketing beyond the merely economic thing. - The satisfaction of desires and needs of the consumers must be placed therefore in the same level that the attainment of the objectives of the organizations. Resumen. El término marketing es de origen inglés y se empezó a utilizar por primera vez en EEUU en la década de los años 20. Se deriva de la palabra inglesa market. Se suele traducir como Mercadología o Mercadotecnia (francés), mercática o mercadeo (hispanos). También se ha traducido como comercialización, pero esta traducción no ha tenido mucho éxito.